Role of Strategic Leadership in Fostering a Culture of Innovation within Organizations - Davis, Joy (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to examine role of strategic leadership in fostering a culture of innovation within organizations Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: strategic leadership plays a pivotal role in fostering a culture of innovation within organizations by guiding and shaping the organizational climate and behaviors that support creativity, risk-taking, and adaptation. Through effective strategic leadership, organizations can cultivate an environment where innovation thrives, driven by visionary leadership, alignment of goals with innovation objectives, and empowerment of employees to explore new ideas and solutions. The study highlighted the significance of leadership styles, organizational culture, and contextual factors in influencing innovation outcomes. Unique Contribution to Theory, Practice and Policy: Transformational Leadership Theory, Organizational Culture Theory & Resource-Based View (RBV) may be used to anchor future studies on role of strategic leadership in fostering a culture of innovation within organizations. Implement leadership development programs that emphasize the cultivation of innovation-supportive behaviors among current and aspiring leaders. These programs should focus on enhancing skills in vision setting, fostering creativity, promoting psychological safety, and aligning organizational goals with innovation objectives. Establish reward systems that recognize and celebrate innovative efforts and successes within the organization. By incentivizing innovation, leaders can reinforce a culture where risk-taking and experimentation are encouraged, fostering continuous improvement and adaptation. Develop policies that create an environment conducive to innovation, such as flexible work arrangements, dedicated resources for research and development, and cross-functional collaboration initiatives. Policies should be aligned with strategic goals and actively supported by top management to ensure consistent implementation and effectiveness.